2012
DOI: 10.1093/eurjhf/hfs026
|View full text |Cite
|
Sign up to set email alerts
|

Gender and survival in patients with heart failure: interactions with diabetes and aetiology. Results from the MAGGIC individual patient meta‐analysis†

Abstract: AimThe aim of this study was to investigate the relationship between gender and survival of patients with heart failure, using data from both randomized trials and observational studies, and the relative contribution of age, left ventricular systolic function, aetiology, and diabetes to differences in prognosis between men and women. Methods and resultsData from 31 studies (41 949 patients; 28 052 men, 13 897 women) from the Meta-Analysis Global Group In Chronic Heart Failure (MAGGIC) individual patient meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

29
121
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 31 publications
(35 reference statements)
29
121
2
3
Order By: Relevance
“…2,3 DM and inflammation is often linked to increased prevalence of heart failure and is known to increase the mortality in patients with heart failure with preserved ejection fraction (HFPEF). [4][5][6][7] The myocardial renin-angiotensin system is locally activated, 8 which contributes to the functional abnormalities and increased cardiovascular risk in DM. 9,10 Indeed, elevated angiotensin II (Ang II) levels lead to cardiac hypertrophy, diastolic dysfunction, and cardiac insulin resistance.…”
mentioning
confidence: 99%
“…2,3 DM and inflammation is often linked to increased prevalence of heart failure and is known to increase the mortality in patients with heart failure with preserved ejection fraction (HFPEF). [4][5][6][7] The myocardial renin-angiotensin system is locally activated, 8 which contributes to the functional abnormalities and increased cardiovascular risk in DM. 9,10 Indeed, elevated angiotensin II (Ang II) levels lead to cardiac hypertrophy, diastolic dysfunction, and cardiac insulin resistance.…”
mentioning
confidence: 99%
“…The risk of death is higher in men than in women with heart failure when adjusted for age (hazard ratio (HR) 1.31, 95% confidence interval (CI) 1.25-1.36, P<0.001). (Adopted from Martínez-Sellés et al 6 )…”
Section: Is There a Sex Difference In Japanesementioning
confidence: 99%
“…6 Data from 31 studies (41,949 patients; 28,052 men, 13,897 women) from the MAGGIC showed that women were older (70.5±12.1 vs. 65.6±11.6 years), more likely to have a history of hypertension (49.9% vs. 40.0%), and less likely to have a history of ischemic heart disease (46.3% vs. 58.7%) and reduced EF (62.6% vs. 81.6%) compared with men. During a 3-year follow-up, 3,521 (25%) women and 7,232 (26%) men died, which was comparable.…”
Section: Editorial Sex Difference In Japanese Hf Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“….min À1 [1][2][3][4][5][6][7][8][9]. I used a lower hazard ratio of 1.5 for the diagnosis of heart failure because I also incorporated the ventilatory equivalent for carbon dioxide in my calculator, for which I used a hazard ratio of 1.05, rather than 1.07 [10].…”
mentioning
confidence: 99%